Iconography and Some Semiotic Concepts: One Velazquez’s Work - Vidaurre, Carmen V. (Eikón / Imago, 2016)
A study of one of the most famous Spanish pictures, known as “Las Meninas”, in which some semiotic concepts are applied to identify textual phenomena with a series of practices and cultural conceptions revealed in the production of canvas, that are expressed in the particular organization of the pictorial signs, in the technical and thematical elements, resources used in the canvas, in which Diego de Silva and Velázquez emphasized the narrative capacity and illusions of the image, and the expression of a temporal dimension and the dynamic happenings.